Cerebello-striatal interaction mediates effects of subthalamic nucleus deep brain stimulation in Parkinson's disease. (October 2019) - Hanssen, Henrike; Steinhardt, Julia; Münchau, Alexander; Al-Zubaidi, Arkan; Tzvi, Elinor; Heldmann, Marcus; Schramm, Peter; Neumann, Alexander; Rasche, Dirk; Saryyeva, Assel; Voges, Jürgen; Galazky, Imke; et al.
Abstract: Background: In Parkinson's disease (PD), dopamine replacement therapy (DRT) enhances the effective connectivity of the prefrontal cortex (PFC) and supplementary motor area (SMA). The clinical effects of deep brain stimulation (DBS) of the subthalamic nucleus (STN) go beyond DRT effects including highly beneficial tremor suppression. Objectives: Here, we aimed to determine DBS-related changes of a motor network using resting state fMRI in PD patients with chronic STN DBS. Methods: In a repeated-measurement design, 26 medicated PD patients (60.9 years (SD 8.9)) were investigated using resting state fMRI while bipolar STN stimulation was (i) active or (ii) switched off, and dynamic causal modelling was subsequently performed. Results: DBS improved the MDS-UPDRS-III score by 26.4% (DBS ON/Med ON vs. DBS OFF/Med ON). Active stimulation resulted in an increased effective connectivity from cerebellum to putamen (p = 0.00118). In addition, there was a stronger coupling from PFC to cerebellum (p = 0.021), as well as from cerebellum to SMA (p = 0.043) on an uncorrected level. Coupling strength from PFC to cerebellum correlated with the DBS-related change of the resting tremor subscore (r = 0.54, p = 0.031). Self-connections increased as a function of DBS in the right PFC, PMC, SMA, M1, thalamus and left cerebellum. Conclusions: DBS-related improvement of Parkinsonian signs appears to be driven by an interaction between the cerebellum and the putamen. Resting tremor suppression may be related to an enhanced prefronto-cerebellar network. Activation of the mesial premotor loop (PFC-SMA) as seen in DRT may thus be secondary due to the primary modulation of cerebellar networks. Highlights: DBS-related improvement of PD tremor seems to be driven by a cerebellar network. STN DBS improves the interaction between cerebellum and striatum. STN DBS upregulates intrinsic connectivity of several brain regions. Basal ganglia and cerebellar loops are strongly interconnected.